A fast and effective method to assess myocardial hyperemia in acute myocarditis by magnetic resonance - Perfetti, Matteo; Malatesta, Gelsomina; Alvarez, Irene; Liga, Riccardo; Barison, Andrea; Todiere, Giancarlo; Eletto, Nicoletta; De Caterina, Raffaele; Lombardi, Massimo; Aquaro, Giovanni Donato (The International Journal of Cardiovascular Imaging, 2014)
Current cardiac magnetic resonance (CMR) quantitative signs for the diagnosis of myocarditis include myocardial edema, fibrosis and myocardial hyperemia (Hyp). Methods for the assessment of Hyp are actually complex and time-consuming. To test a simple and fast method to assess Hyp, using contrast enhancement steady state free precession (ceSSFP) technique. CMR imaging at 1.5T was performed on 39 patients with diagnosis of acute myocarditis and in 20 healthy controls. Hyp was evaluated in systolic and diastolic frames (Hyp-SYS and Hyp-DIA) as areas of myocardial hyperintensity in ceSSFP images early after gadolinium injection. Myocardial edema was evaluated using T2-STIR images. Myocardial fibrosis was assessed in conventional late gadolinium enhancement (LGE) images. A value of ≤12.1 g of Hyp-DIA was obtained as cut-off of normality in healthy controls. Using this threshold, Hyp was detected in 30 patients (77 %) with myocarditis. LGE was detected in 36 patients (92 %), and myocardial edema in 38 (97 %) patients with myocarditis A linear relation was found between Hyp-DIA and the extent of myocardial edema (R 2 0.48, 95 % CI 0.47–0.85, p < 0.001) and the extent of LGE (R 2 0.41, 95 % CI 0.31–0.61, p < 0.001). Patients with hyperemia had higher levels of C-reactive protein ( p < 0.001), a higher extent of LGE ( p < 0.05) and a larger left atrial area ( p < 0.05). ceSSFP sequence at CMR is a novel and fast method to assess myocardial hyperemia in patient with acute myocarditis. Compared with non-Hyp subjects, patients with Hyp had more signs of inflammation and myocardial damage.